Eksplorasi Konstruksi Identitas Guru Sains Melalui Berbagai Konteks Pengalaman Hidup - Herdhiyani, Ari Dhinansah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Identity is the construction of interpretations of life experiences in certain contexts resulting in self-understanding. This research with a single case study design aims to explore the identity of science teachers in various contexts of Figured Worlds. The research participant is a science teacher named Yuni who has a background in Physics Education. Data were collected through two semi-structured interviews. The results revealed how Yuni interpreted science-related life experiences in Figured Worlds to construct her identity. The researcher concluded that although throughout Yuni's experience she was not interested in becoming a teacher, she was able to become an outstanding teacher through her scientific papers.